Disitamab vedotin (RC48) long-term regimen in a post-nephroureterectomy patient with metastases: a case report - Li, Weiping; Jing, Suoshi; Zhao, Bo; Jiang, Wei; Zhang, Bin (Frontiers in Oncology, 2024)
BackgroundFor patients with metastatic upper tract urothelial carcinoma (UTUC), the preferred first-line treatment is platinum-based chemotherapy. Immunotherapy can be considered a subsequent treatment if the chemotherapy is ineffective or the disease progresses. However, how should treatment be administered if immunotherapy is useless and the patient cannot take chemotherapy? Especially in patients who have metastasized after radical nephroureterectomy (RNU).Case presentationA 68-year-old woman was admitted to the hospital due to left flank pain for two weeks and was diagnosed with metastatic UTUC after RNU. The patient underwent systemic chemotherapy with gemcitabine and cisplatin (GC), as well as reduced-dose GC, but developed myelosuppression. Immunotherapy was ineffective, so Disitamab vedotin (RC48) was chosen.ResultsDisitamab vedotin (RC48) monotherapy was administered for 13 cycles, during which thyroid function remained normal, the patient responded well to the treatment, and the disease was controlled well. In the subsequent two years of follow-up, there was no disease recurrence.ConclusionThe long-term treatment regimen with RC48 is feasible for metastatic UTUC after RNU, and RC48 monotherapy is suitable as first-line therapy for selected patients.